Effectiveness of the Free Nutritious Meal (MBG) Program on Nutritional Status, Learning Concentration, and Student Attendance in South Jakarta Elementary Schools - Wahyuniar, Lely; Iman Pustakasari, Endahing Noor (Jurnal Medisci, 2025)
Background. Malnutrition remains a major global health challenge affecting millions of school-aged children. Adequate nutrition during childhood is essential for optimal physical growth, cognitive development, and learning achievement Aims. This study aimed to evaluate the effectiveness of the Free Nutritious Meal (Makan Bergizi Gratis/MBG) Program on the nutritional status, concentration in learning, and attendance of public elementary school students in Kebayoran Lama District, South Jakarta. A quantitative descriptive case–control design was used, involving 200 students from two public elementary schools—100 MBG beneficiaries and 100 non-beneficiaries. Methods. Data were collected using a validated questionnaire measuring students’ perceptions of the MBG program, nutritional status, learning concentration, and attendance, complemented by BMI records and structured observations. Statistical analyses included Shapiro–Wilk, Mann–Whitney U, Chi–Square, MANOVA, and Odds Ratio tests. Results showed that the MBG program significantly improved students’ perceptions of its impact and contributed to better nutritional status in the experimental group, although improvements in learning concentration were not statistically significant. Attendance remained higher among control students, suggesting the influence of external factors such as family or environmental conditions. Conclusion. The MBG Scale demonstrated good validity and reliability (Cronbach’s α = 0.65–0.73). Overall, the MBG program positively influenced students’ nutritional status and perceptions of program benefits, but had limited effects on cognitive and attendance outcomes. Implementation. Strengthening program implementation quality, expanding coverage, and integrating psychological and family support components are recommended to enhance its effectiveness and sustainability.